2021
DOI: 10.3389/fnut.2021.684438
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Is Associated With Impaired Functional Status in Older People Receiving Home Care Nursing Service

Abstract: Objective: This study aimed to explore the magnitude and significance of associations among nutritional status, functional status, comorbidities, age, and gender in older adults receiving assistance from the in-home nursing care service.Method: In this cross-sectional study, 210 home-dwelling persons 65 years or older who received in-home nursing care service were evaluated. Demographic variables, nutritional status, comorbidities, and the dependency levels of activities of daily living were analyzed. To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…Additionally, identifying subjects with functional impairment would allow the placement of appropriate medical–nutrition strategies to avoid physical dependence, which could improve the life quality of subjects [ 27 , 28 ]. It is important to note that malnutrition and functionality impairment have a negative impact on healthcare systems and in several scenarios that involve patients, owing to increased hospital expenditures, drug consumption and length of recovery time [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, identifying subjects with functional impairment would allow the placement of appropriate medical–nutrition strategies to avoid physical dependence, which could improve the life quality of subjects [ 27 , 28 ]. It is important to note that malnutrition and functionality impairment have a negative impact on healthcare systems and in several scenarios that involve patients, owing to increased hospital expenditures, drug consumption and length of recovery time [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, nutritional status evaluated using the MNA showed a significant association with discharge location and geriatric syndrome, whereas nutritional status evaluated using serum albumin had no significant association. This may be because the MNA has the advantage of predicting functional decline ( 49 , 50 ). The fact that the MNA is a multidimensional tool that includes general assessment, dietary assessment, and anthropometric assessment can make this prediction possible ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Short Form, available on Nestlé's website, was developed and validated specifically for an older population (>60 years) [2]. Completion of the MNA-SF results in a score with 3 categories: normal (12)(13)(14), risk of malnutrition (8)(9)(10)(11), and malnourished (0-7).…”
Section: Mini Nutritional Assessment Short Form (Mna-sf)mentioning
confidence: 99%
“…Nursing homes must deal with large numbers of senior citizens, often with a wide range of pathologic conditions and clinical status, from active aging seniors to very dependent older patients. Studies have reported that malnutrition is directly associated with the functional impairment of senior populations, and nutritional status is indirectly associated with the presence and severity of comorbidities [7,8]. Given the diversity and number of senior citizens that require assessment, nursing homes have a need to identify simple, inexpensive, and fast tools to assess nutritional risk and/or status in order to save time for health professional and reduce inconvenience to the senior population [9].…”
Section: Introductionmentioning
confidence: 99%